KEMAMPUAN MEMBACA TEKS CERPEN DAN MENULIS TEKS ULASAN CERPEN SISWA KELAS VIII SMP NEGERI 23 PEKANBARU - Novryanti Rahayu; Abdul Razak; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is titled Ability to Read Short Text and Writing short story text Review of VIII Grade Students of SMP Negeri 23 Pekanbaru. This study aims to describe the ability to read the text of the story of the students of class VIII SMP Negeri 23 Pekanbaru, to describe the different or not the ability to read the short story text of the students of grade VIII SMP Negeri 23 Pekanbaru among sample groups, to describe the ability to write the text of the students of class VIII SMP Negeri 23 Pekanbaru different or not the ability to write the text of the clever class review of students VIII 23 Pekanbaru, and describes the relationship between the ability to read short story text and write text short story reviews. The data of this research is the result of the reading ability test of short story text and writing the text of the story of the students of class VIII SMP Negeri 23 Pekanbaru which is spread over 8 classes with the population of 159 students and the number of samples is 115 students. Technique of collecting data that is giving test read short story text and writing text of short story. To find out whether or not the expected score and the results of the scores obtained by the students were calculated using the Wilcoxon test, to determine whether there was a difference or not in the mean between groups the sample was calculated using the Kruskall-Walis test, and to find the relationship of reading ability of short story text and writing the text of the calculated short story using correlation ladder. Based on the result of research, it is found that: (1) the ability to read the short story text of the students of grade VIII SMP Negeri 23 Pekanbaru is low, (2) the ability to read the short story text between the sample groups there is no difference, (3) the ability to write the text of the students of grade VIII SMP Negeri 23 Pekanbaru is low, (4) ability to write text of short story between different group of samples. The meaning, there are differences in the ability to write short story textbooks among fellow students of class VIII, (5) the ability to read short story text and write the text of the short story has a low opinion of the correlation coefficient correlation coefficient of 0.21-0.40.Key words: ability, reading, writing, short story text, review text